Utilization and associated factors of sexual and reproductive health services among adolescents of Kathmandu district, Nepal - Pokhrel, Sushma; Nepal, Susmita; Mali, Prajita; Baskota, Swechhya; Aryal, Richa; Thapa, Alisha; Chaudhary, Vidya; Malla, Nabina (International Journal Of Community Medicine And Public Health, 2020)
Background: There seems to be huge differences in availability and utilization of Sexual and Reproductive Health information and services despite of taking decisive step by Government of Nepal. The main aim of the study is to access the utilization and factors associated with SRH services among adolescents. Methods: This cross-sectional descriptive study was carried out among 406 adolescent students of grade 11 and 12 which were taken as census in selected higher secondary schools of Kathmandu District through simple random sampling technique. The utilization of SRH services was assessed by semi-structured validated and pretested questionnaire which includes socio-demographic, utilization of sexual health and reproductive health (SRH) services and sexual behaviours. Data were entered and analyzed in SPSS version 20 where Chi-square tests is done to identify the associated factors with utilization SRH services utilization. Results: Overall utilization in last 12 months was 17.2% and was found to be strongly associated with availability of services within 30 minutes of walking distance (p value=0.001), interaction with parents (p-value: 0.02) and with sexually being active within 12 months (p value=0.001). Utilization of SRH services was slightly higher among females (19.8%) compared to males (15.3%). Most utilized services were services related to menstrual problems and family planning including ECP. This study concludes that fear of family and society hinders the utilization of SRH services. Conclusions: As adolescent fear to talk and seek for the services, due to the social cultural norms and stigma attached to SRH services, utilization among adolescent of selected colleges in Kathmandu is low.